Some aspects of the legal and regulatory framework of accounting and analytical process of the current assets of the enterprise - Shmatkovska, Tetiana О.; Polishchuk, K. O.; Шматковська, Тетяна Олександрівна; Поліщук, Ксенія Олександрівна (Ужгородський національний університет, 2016)
The article analyzes the regulatory and legal framework for accounting of current assets, provides a list of defini- tions, interpretations about the essence of current assets by various scholars, generalized types of current assets, and are the main legislative acts regulating accounting current assets in enterprises. У статті проаналізовано нормативно-правове забезпечення обліку оборотних активів, проведено систематизацію трактувань сутності оборотних активів різними вченими, узагальнено види оборотних активів, а також наведено основні законодавчі акти, що регулюють облік оборотних активів на підприємстві. В статье проанализировано нормативно-правовое обеспечение учета оборотных активов, систематизированы трактовки сущности оборотных активов различными учеными, обобщены виды оборотных активов, а также приведены главные законодательные акты, регулирующие учет оборотных активов на предприятиях.
Деякі аспекти нормативно-правових засад обліково-аналітичного процесу оборотних активів підприємства
Keywords: the current assets; inventories; receivables; cash and cash equivalents; the regulatory support; the accounting and analytical process; оборотні активи; запаси; дебіторська заборгованість; грошові кошти та їх еквіваленти; нормативно- правове забезпечення; обліково-аналітичний процес; оборотные активы; запасы; дебиторская задолженность; денежные средства и их эквиваленты; нормативно-правовое обеспечение; учетно-аналитический процесс